2014
DOI: 10.1097/xce.0000000000000014
|View full text |Cite
|
Sign up to set email alerts
|

Blunted neuroendocrine responses linking depressive symptoms and ECG-left ventricular hypertrophy in black Africans

Abstract: Objective Chronic psychosocial stress as experienced in an urban environment plays an important role in the aetiology of depression-related cardiovascular risk. It is uncertain whether acute mental stress responses aggravate this risk. Therefore, we aimed to explore the associations between depressive symptoms, neuroendocrine acute mental stress responses and cardiovascular risk, that is ECG-left ventricular hypertrophy (ECG-LVH), in a black South African cohort. Materials and methodsThe substudy sample consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
(52 reference statements)
2
10
0
Order By: Relevance
“…Considering sex differences; African men in the low cortisol category have a ten times higher risk of increased ACR, than those in the high cortisol category. This confirms results from previous studies, where African men revealed attenuated cortisol responses associated with structural wall remodelling [32] and poorer health than their female and Caucasian counterparts [2,13,32,42]. From these results, it is evident that African men with low or possible down-regulated cortisol levels reveal more vulnerability for renovascular disease than their high cortisol as well as Caucasian counterparts.…”
Section: Low Cortisol and Renal Impairmentsupporting
confidence: 93%
See 2 more Smart Citations
“…Considering sex differences; African men in the low cortisol category have a ten times higher risk of increased ACR, than those in the high cortisol category. This confirms results from previous studies, where African men revealed attenuated cortisol responses associated with structural wall remodelling [32] and poorer health than their female and Caucasian counterparts [2,13,32,42]. From these results, it is evident that African men with low or possible down-regulated cortisol levels reveal more vulnerability for renovascular disease than their high cortisol as well as Caucasian counterparts.…”
Section: Low Cortisol and Renal Impairmentsupporting
confidence: 93%
“…The HPAA thus seems to have become non-responsive or hypoactive to stress in these participants. Possible down-regulation occurred, decreasing sensitivity of the HPAA and adrenal fatigue may have set in, with subsequent lower levels of cortisol [24,32,[38][39][40]. Thus, with further exposure to stress, the desensitised or habituated HPAA defensive coping response may not be able to increase cortisol for effective coping, and becomes dysfunctional.…”
Section: Low Cortisol Versus High Cortisolmentioning
confidence: 97%
See 1 more Smart Citation
“…During chronic stress, a maladaptive cortisol response is elicited due to structural changes in the HPA axis 21-23. A state of psychological distress in Africans may therefore be present 12,19,20…”
Section: Discussionmentioning
confidence: 99%
“…If this state is further supported by high levels of alcohol abuse, the central depressant effect of alcohol may disturb central cardiometabolic homeostasis 21. Chronic psychological stress induces sympathetic hyperactivity,17 higher circulating levels of catecholamine and cortisol, and ultimately down-regulation will occur 12,22-24. Therefore, the lower cortisol level may act as the driving force behind a possible down-regulated BDNF.…”
Section: Discussionmentioning
confidence: 99%